2011
DOI: 10.1007/s10461-011-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal Cleansing Practices in HIV Infected Zambian Women

Abstract: Vaginal practices are a variety of behavioral techniques that women use to manage their sexual life and personal hygiene. Women perceive vaginal practices as a beneficial practice. However, vaginal cleansing has been identified as one of the main risk factors for bacterial vaginosis and is potentially implicated in Human Immune Deficiency Virus (HIV) and sexually transmitted infection transmission. This study examined the prevalence of vaginal practices and the types of practices used among a sample of HIV pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 14 publications
1
42
0
Order By: Relevance
“…Preliminary data for this study identified individual beliefs and practices in this community and has previously been published. 15 Three focus groups consisting of ten women each and one focus group of ten men were conducted by gender-matched female and male facilitators. Key informant interviews with three female Alengizis were conducted by a female interviewer.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preliminary data for this study identified individual beliefs and practices in this community and has previously been published. 15 Three focus groups consisting of ten women each and one focus group of ten men were conducted by gender-matched female and male facilitators. Key informant interviews with three female Alengizis were conducted by a female interviewer.…”
Section: Methodsmentioning
confidence: 99%
“…IVP that include insertion of products to promote dry sex leads to genital abrasions that can facilitate HIV acquisition and transmission. 3,4,7,8,[13][14][15] IVP are strongly influenced by social and cultural beliefs, introduced to women at an early age, and normally taught by older females (relatives, friends, or traditional marriage counselors). 15,16 Although IVP are female initiated and intended to be conducted without the explicit knowledge of men, many IVP are driven by male preferences.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations